Internationalization of the Chinese Renminbi - Rao, Qu; Brůna, Karel, 1973-; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This study investigates the macroeconomic determinants of Renminbi (RMB) internationalization, using the scale of RMB deposits in Hong Kong (LNRMBD) as a proxy indicator. Drawing on annual data from 2004 to 2023, the analysis employs a Vector Error Correction Model (VECM) to examine both the short-run dynamics and long-run equilibrium relationships between RMB internationalization and four key macro-financial variables: China's GDP growth rate (LNGDPR), foreign exchange reserves (LNFER), stock market capitalization-to-GDP ratio (LNMCG), and the real effective exchange rate of the RMB (LNREER). The Johansen cointegration test confirms the presence of a longrun equilibrium relationship among the variables. The adjustment coefficient (α) for LNRMBD is negative and highly significant, indicating a strong adjustment mechanism. In the short run, LNMCG and LNGDPR exert significant positive effects. Granger causality tests identify unidirectional causality from LNMCG and LNGDPR to LNRMBD. Impulse response functions reveal that one-standard-deviation shocks to LNMCG and LNFER generate strong and persistent positive effects on RMB deposits, while shocks to LNGDPR are negligible and LNREER has a weakly negative impact. Variance decomposition further highlights the dominant roles of LNMCG and LNFER in explaining fluctuations in offshore RMB deposits. These findings emphasize the importance of financial development and external credibility in advancing RMB internationalization.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses